Analisis Penggunaan Metode Penelitian Evaluasi Pada Penelitian Bahasa Arab Model Pengembangan - Khoirul Faizin (TABYIN: JURNAL PENDIDIKAN ISLAM, 2020)
Penelitian Development research is one of the studies that focuses on new products as its output. In addition to the need for creative ideas in this research also need to use several methods in the development process. One method that is needed in this research model is the evaluation research method. Evaluation method is a type of method used to find the strengths and weaknesses of a system or product which is then translated into needs analysis. This study uses a qualitative descriptive approach, because the aim is to describe and describe what it is about a particular variable, phenomenon, state or social phenomenon. Data collected according to the focus of research in the form of words, actions, situations, documentation and events observed. In this analysis it was found that from the many exposures of experts about development research there was one similarity in the patterns that researchers found. The similarity is related to the process or procedure of the research stage carried out. Some of the stages of the research are a) Research and Data Collection, b.) Requirement Analysis, c.) Product Development, d.) Field trials, e.) Revision or Refinement of Final Products f.) Multiplication and use of mass products.